The Digital Political Revolution: The Impact of Artificial Intelligence (AI) Based Political Campaigns on Voter Perceptions and Decisions in Generation Z In Indonesia - Febriandy, Radians Krisna; Revolusi, Prabu (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
Rapid technological advances are transforming artificial intelligence (AI) into a very powerful tool in political campaigns, almost all digital platforms make it possible to personalize content and connect directly to voters. The purpose of this study is to explain the influence of AI-based political campaigns on the perceptions and decisions of Generation Z voters in Indonesia. This research uses a quantitative approach with a survey method to 395 respondents aged 17-29 years, active in various social media and participating in the 2024 Presidential Election. The results of the study explain that the effect of artificial intelligence (AI)-based political campaigns on perceptions is 91.5% and voter decisions is 96.7%, this explains that artificial intelligence (AI)-based political campaigns have a very significant influence on the perceptions and decisions of Generation Z voters in Indonesia. The practical implications of AI-based political campaigns include being able to personalize campaigns more effectively, optimizing campaign resources, managing candidate images, increasing voter interaction, and monitoring and regulating ethics.